THE RELIGIOUS AND CULTURAL TRADITIONS OF ANCIENT INDIAN PERIOD WITH SPECIAL REFERENCE TO BUDDHISM - Sivasai, Chintala Venkata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Though it is far more than just a standard moral instruction, Buddhist ethics includes a great code of ethics, including one for the Saṃgha (monks and nuns) and another for the general public. Sīla, or morality, is merely the first step and a means to an aim rather than an end in and of itself. Despite being very necessary, it does not bring about salvation or complete purity on its own. On the journey to purity, it is but the beginning. Wisdom (Paňňā) is superior to morality. Buddhism's peak is wisdom, while its foundation is morality. These two complementing qualities are similar to a bird's pair of wings. Morality is like a person's feet, and wisdom is like his eyes. One of the Buddha's names is Vijjācaraṇasaṃpanna, which means "endowed with wisdom and conduct." The first three of the Four Noble Truths, which serve as the cornerstone of Buddhism, stand for the Buddha's teaching philosophy; the fourth is the ethics of Buddhism, which is founded on that philosophy.